Trowulan Sebagai Historic City: Mengkonstruksi Citra Melalui Pengelolaan Informasi - Sugeng Riyanto (Berkala Arkeologi, 2004)
The Trowulan site in Mojokerto Regency, East Java, is one of the important sites that is utilized both ideologically, academically and economically at the same time. Since Wardenaar, who was assigned by Sir Thomas Raffles to observe ancient relics in Mojokerto, and in 1815 succeeded in making documents in the form of pictures and descriptions, the urge to research this site is getting bigger, even today. One of the striking results of the research is that the archeology is very closely related to the Majapahit Kingdom, the last Hindu work in Java which flourished from 1293 to 1478. In particular, the various scattered relics indicate that Trowulan was an ancient city. Not only that, other archaeological activities, namely conservation, are also being carried out to this day.